Hydrophobic Interactions Drive the Attachment of a Model Nanoplastic on Porous Media Surfaces - Youssra Rahham; Marios A. Ioannidis (Water Resources Research, 2025)
Abstract Predicting the transport and fate of nanoparticles in the subsurface requires understanding of their interactions with collector surfaces. We report here on the effect of the less‐studied hydrophobic interactions, which are relevant to the fate of hydrophobic nano‐colloids. Using a model nanoplastic (charge‐stabilized, ethyl cellulose nanoparticles) and a model porous medium (regular array of collectors in a pore network etched on glass) we demonstrate the dominance of hydrophobic attraction over electrostatic repulsion when an otherwise hydrophilic glass surface is rendered hydrophobic via coating with octadecyltrichlorosilane (OTS). An empirical model of hydrophobic interactions between dissimilar surfaces (Yoon et al., 1997, https://doi.org/10.1006/jcis.1996.4583), informed by contact angle measurements, explains the irreversible attachment of ethyl cellulose nanoparticles on OTS‐coated glass surfaces confirmed by atomic force microscopy. Transport of ethyl cellulose nanoparticles in OTS‐coated glass micromodels is characterized by favorable irreversible attachment. These findings provide novel insights into the mechanisms affecting the transport and fate of nano‐colloids in subsurface aquatic environments and lend further support to the conclusion that contact angle can serve to quantify the magnitude of hydrophobic interactions between nanoparticles and collector surfaces.